Examining the Role of Gender, Job Status, Marital Status, and Semester Level on General Self- Efficacy and Social Self- Efficacy of Management Students - Shrestha, Indira (Contemporary Research: An Interdisciplinary Academic Journal, 2025)
This study examined the effect of gender, job status, marital status, and level of semester on general self-efficacy and social self-efficacy of management students. The study employed quantitative approaches along with statistical tools like independent sample and one-way ANOVA to assess the role of demographic status on general and social self-efficacy. The population of the study is students who were studying in the Master of Business Studies (MBS) program of Tribhuvan University’s constituent campuses located in Kathmandu Valley. Responses were collected through a self-administered questionnaire general self-efficacy and social self-efficacy scale developed by Sherer et al. (1982), using convenience sampling. Regarding results, except for marital status of the students, gender, job status, and semester level did not affect the general self-efficacy. Based on the overall mean value, students have general self-efficacy, while they are neutral in the case of social self-efficacy. Gender, job status, marital status, and semester level did not affect social self-efficacy. The students will learn the importance of self-efficacy to succeed in their personal and professional lives. This also adds value to efficacy theory and also whether the demographics of students affect their self-efficacy level.